Mapping relational links between motor imagery, action observation, action-related language, and action execution - O’Shea, Helen (Frontiers in Human Neuroscience, 2022)
Actions can be physically executed, observed, imagined, or simply thought about. Unifying mental processes, such as simulation, emulation, or predictive processing, are thought to underlie different action types, whether these actions are mental states, as in the case of motor imagery and action observation, or involve physical execution. In support of such commonalities, overlapping brain activity is typically observed during mental and physical action. Recently, research interest has been directed towards investigating the idea that different mental actions may also possess distinct functional components. Unfortunately, untangling subtleties associated with the neurocognitive bases of different action types, whether they are mental or physical, is a complex endeavour due to the high dimensional nature of their neural substrate (e.g., any action process is likely to activate multiple brain regions thereby having multiple dimensions to consider when comparing across them). This has impeded progress in action-related theorising and application. The present study addresses this challenge by using the powerful statistical approach of multidimensional scaling, to reduce the 82 dimensions (i.e., 82 brain regions) of the neural substrate for different action types (motor imagery, action observation, action-related language, and action execution) to a three-dimensional model. Data for the model comprised brain activations from whole-brain analyses for the different action types from 53 published papers. The final 3-dimensional model mapped action types in ordination space where the greater the distance between the action types, the more dissimilar they are. Similarities and dissimilarities were observed between action types, indicating both shared and unique neurocognitive substrate.